Effect of Problem-Based Learning on Vocational Students’ Creative Products and Entrepreneurship (PKK) Outcomes in an Indonesian Public Vocational School - Chairunnisa Biahimo; Roy Hasiru; Sudirman Sudirman; Meyko Panigoro; Ardiansyah Ardiansyah (Yayasan Pendidikan Sudirman Mandiri, 2026)
Entrepreneurship-oriented learning in vocational schools requires instructional approaches that promote active inquiry, practical competence, and meaningful engagement. This study examined the effect of problem-based learning on Grade XI students’ learning outcomes in Creative Products and Entrepreneurship at SMK Negeri 4 Gorontalo. A quantitative, causal design was used with total sampling of 32 students. Data were collected using structured questionnaires and supporting documentation, and were analysed using simple linear regression with assumption checking through a residual normality test. Results show that students perceived problem-based learning implementation as very strong across its core stages, and learning outcomes were similarly rated very highly across cognitive, affective, and psychomotor domains. The regression model indicates a positive association between problem-based learning and learning outcomes, supported by a statistically significant coefficient. The relationship is strong, and the model explains more than half of the variance in learning outcomes, suggesting that problem-based learning is a substantial instructional contributor to entrepreneurship-related attainment in this context. Nonetheless, a meaningful proportion of outcome variance remains linked to other influences. These findings indicate that consistent implementation of problem-based learning can improve vocational students’ entrepreneurial learning outcomes and that optimisation efforts should be complemented by supportive conditions such as adequate learning facilities and motivational supports.